Hepato-protective effects of six schisandra lignans on acetaminophen-induced liver injury are partially associated with the inhibition of CYP-mediated bioactivation. (25th April 2015) - Jiang, Yiming; Fan, Xiaomei; Wang, Ying; Tan, Huasen; Chen, Pan; Zeng, Hang; Huang, Min; Bi, Huichang
Highlights: Six schisandra lignans exerted significant protective effects against APAP toxicity. SinC and SolB possessed the strongest hepato-protective actions. Pretreatment with six lignans prevented hepatic GSH depletions caused by APAP. Some of the lignans inhibited the enzymatic activities of CYP2E1, CYP1A2, and CYP3A11. Some of the lignans significantly decreased the NAPQI formation. Abstract: Acetaminophen (APAP) overdose is the most frequent cause of drug-induced acute liver failure. Schisandra fructus is widely-used traditional Chinese medicine which possesses hepato-protective potential. Schisandrin A (SinA), Schisandrin B (SinB), Schisandrin C (SinC), Schisandrol A (SolA), Schisandrol B (SolB), and Schisantherin A (SthA) are the major bioactive lignans. Most recently, we found SolB exerts significant hepato-protection against APAP-induced liver injury. In this study, the protective effects of the other five schisandra lignans against APAP-induced acute hepatotoxicity in mice were investigated and compared with that of SolB. The results of morphological and biochemical assessment clearly demonstrated significant protective effects of SinA, SinB, SinC, SolA, SolB, and SthA against APAP-induced liver injury. Among these schisandra lignans, SinC and SolB exerted the strongest hepato-protective effects against APAP-induced hepatotoxicity. Six lignans pretreatment before APAP dosing could prevent the depletions of total liver glutathione (GSH) and mitochondrial GSH caused by APAP. Additionally, the lignans treatment inhibited the enzymatic activities of three CYP450 isoforms (CYP2E1, CYP1A2, and CYP3A11) related to APAP bioactivation, and further decreased the formation of APAP toxic intermediate N -acetyl-p-benzoquinone imine (NAPQI) in mouse microsomal incubation system. This study demonstrated that SinA, SinB, SinC, SolA, SolB and SthA exhibited significant protective actions toward APAP-induced liver injury, which was partially associated with the inhibition of CYP-mediated APAP bioactivation.